QUALITY ANALYSIS OF THE LAPKIN WEBSITE SYSTEM USING THE WEBQUAL 4.0 METHOD AT DEPARTMENT OF THE ENVIRONMENT AND CLEANING PALEMBANG CITY - Tri Oktarina; Tobi Feriansyah (Informatika, Universitas Jenderal Soedirman, 2022)
The LAPKIN website is one of the websites in the form of the Republic of Indonesia's State Civil Apparatus (ASN) Annual Performance Report. The LAPKIN website itself is intended for Central Government Agencies and Regional Agencies. The functions or advantages are to facilitate ASN in submitting the Annual Performance Reports carried out by each agency, and to be able to view agency profiles, organizational structures, work units, job titles, work performance, absenteeism permits, comparison charts of annual assessments and employee status . With the construction of the LAPKIN website, it is hoped that it can assist the tasks of central/regional agencies in carrying out employee performance reporting. In this study it is important to know the quality of the system from the LAPKIN website (Performance Report) at the Palembang City Environment and Hygiene Service, therefore this study aims to analyze the quality of the LAPKIN website system using the WebQual 4.0 method which consists of 3 variables, namely usability, quality information, and the quality of service interactions. The results of this study can provide recommendations to the Environmental and Hygiene Agency of Palembang City to improve the level of website quality in order to achieve maximum utilization.